Thomson–Einstein’s Tea Leaf Paradox Revisited: Aggregation in Rings - Kirill Kolesnik; Daniel Quang Le Pham; Jessica Fong; David John Collins (Micromachines, 2023)
A distinct particle focusing spot occurs in the center of a rotating fluid, presenting an apparent paradox given the presence of particle inertia. It is recognized, however, that the presence of a secondary flow with a radial component drives this particle aggregation. In this study, we expand on the examination of this “Thomson–Einstein’s tea leaf paradox” phenomenon, where we use a combined experimental and computational approach to investigate particle aggregation dynamics. We show that not only the rotational velocity, but also the vessel shape, have a significant influence on a particle’s equilibrium position. We accordingly demonstrate the formation of a single focusing spot in a vessel center, as has been conclusively demonstrated elsewhere, but also the repeatable formation of stable ring-shaped particle arrangements.